KONVERGENSI TINGKAT PENDAPATAN STUDI KASUS 3 PROPINSI DI PULAU JAWA - Heriqbaldi, Unggul (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2009)
The objective of this paper is to examine the income convergence in three provincesin Java island such as West Java, Central Java, and East Java during time period2004-2007. Using Â two concepts of convergences which are ï¢-convergence and ï³-convergence, this paper show that in three regions Â there not found ï¢-convergenceand ï³-convergence. This result indicated Â that Â in Â three provinces, Â if there were anincreasing Â in Gross Domestic Regional Product Â (GDRP), Â it always espoused withenhancing in growth GDRP, and enhancing in the gap Â level in one regency to Â theother regency. This means that the estimation result exactly confirmed the happeningof economy development with divergence not convergence.Keywords: income convergences, regional economics, and divergence